(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
This article examines the objects, subjects and problems in the functioning, management and prospects of development of venture capital companies and funds, path «exit» from the business venture investors in the current economic conditions. The factors accelerate the development of venture capital, such as the presence of concentrated placement of objects venture infrastructure in one area that will enable you to create innovative company with less overhead. Decision of question of forming of infrastructure, will allow to develop a venture enterprise and on his basis to carry out the innovative breach of development of economy of Ukraine